2023
DOI: 10.3390/nu15051216
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-Hydroxyvitamin D Is Differentially Associated with Early and Late Age-Related Macular Degeneration in the United States Population

Abstract: Background: Age-related macular degeneration (AMD) has been the leading cause of irreversible blindness in industrialized countries. Emerging data suggest that serum vitamin D levels may be associated with AMD but show mixed results. National-level population data on the relationship between vitamin D and AMD severities are still lacking. Methods: We used data from the National Health and Nutrition Examination Survey (NHANES) 2005 to 2008. Retinal photographs were taken and graded for AMD stage. The odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
0
0
Order By: Relevance
“…In the most literature reviews, it can be observed that some authors of publications are of the opinion that low vitamin D levels may influence the frequency of disease occurrence. [5,6,8,12,25,35] However, a different study found that a higher concentration of vitamin D in the serum was linked to an increased likelihood of early AMD and a decreased likelihood of late AMD [24], while according to another article, a high level of vitamin D was associated with a lower likelihood of developing early AMD. [8] In different study, researchers concluded that the concentration level of vitamin D has no influence on the occurrence of AMD.…”
Section: Discussionmentioning
confidence: 99%
“…In the most literature reviews, it can be observed that some authors of publications are of the opinion that low vitamin D levels may influence the frequency of disease occurrence. [5,6,8,12,25,35] However, a different study found that a higher concentration of vitamin D in the serum was linked to an increased likelihood of early AMD and a decreased likelihood of late AMD [24], while according to another article, a high level of vitamin D was associated with a lower likelihood of developing early AMD. [8] In different study, researchers concluded that the concentration level of vitamin D has no influence on the occurrence of AMD.…”
Section: Discussionmentioning
confidence: 99%
“…However, among individuals older than 60, it was linked to a reduced risk of late AMD. The same study suggests that maintaining serum 25(OH)D within certain levels may have benefits in reducing the risk of AMD for at-risk individuals [ 44 ]. There seems to be a tendency for late-stage AMD in humans whose serum vitamin D levels are below 50 nmol/L [ 45 ].…”
Section: Age-related Macular Degeneration (Amd)mentioning
confidence: 99%